Coexistence of Two Invasive Species, Procambarus clarkii and Aphanomyces astaci, in Brackish Waters of a Mediterranean Coastal Lagoon - Martín-Torrijos, Laura; Correa-Villalona, Angel Jose; Pradillo, Antonio; Diéguez-Uribeondo, Javier (Frontiers in Ecology and Evolution, 2021)
Procambarus clarkii is a worldwide freshwater invasive crustacean from North America and was first introduced into Europe the 1970s. Along with P. clarkii, another invasive alien species was also spreading: Aphanomyces astaci. This pathogen is listed among the 100 World´s worst invasive species and involved in the European native crayfish decline. Although both species live in freshwater ecosystems, P. clarkii can withstand brackish waters and inhabit estuarine habitats. However, the presence of A. astaci associated to North American crayfishes has never been described in brackish waters. In this study, we have investigated the presence of A. astaci in a P. clarkii population of a Mediterranean coastal lagoon in the Albufera Natural Park, Valencia, Spain introduced in 1976. Our study confirmed the presence of this pathogen, and suggests that A. astaci has been spreading for more than four decades in the mentioned estuarine environment. Mitochondrial ribosomal rnnS and rnnL indicated that the isolated pathogen belongs to d1-haplotype (i.e., D-haplogroup) typically hosted by P. clarkii. The presence of this pathogen in a brackish environment may suggest a better adaptation than other A. astaci strains to adverse conditions, such as high salinity levels. This is a matter of concern for the conservation of European native freshwater crayfish and highlights once more the risk of introducing invasive alien crustaceans.